The Utilization of IoT in Real-time Temperature and Humidity Monitoring Using Microcontroller: A Literature Review - Fachrul Rizky Syaputra (Yayasan Kita Menulis - JoCPES, 2023)
Temperature and humidity must be considered in various fields such as weather, agriculture, technology and industry. The Internet of Things (IoT) can be applied in temperature and humidity monitoring systems so that the data obtained is real time. The research uses a literature review method that has the main goal of searching journals through Google Scholar. This study analyzes the use of IoT for temperature and humidity monitoring using various sensors such as DHT22, DHT11, and DS18B20 in various fields. Based on several journals from 2017 to 2024, it was selected to provide an understanding of the effectiveness and accuracy of different types of sensors in environmental monitoring. The results of the study show that IOT makes it easier to monitor environmental conditions efficiently and accurately, helping to make decisions quickly and automatically. The DHT22 sensor is effective for monitoring due to its low cost and good quality, while DS18B20 excels in accuracy. This research is useful in the development of IoT in various environmental monitoring needs.